Centriolar satellites are assembly points for proteins implicated in human ciliopathies, including oral-facial-digital syndrome 1 - Carla A.M. Lopes; Suzanna L. Prosser; Leila Romio; Robert A. Hirst; Chris O’Callaghan; Adrian S. Woolf; Andrew M. Fry (2011)
Ciliopathies are caused by mutations in genes encoding proteins required for cilia organization or function. We show through colocalization with PCM-1, that OFD1 (the product of the gene mutated in oral-facial-digital syndrome 1) as well as BBS4 and CEP290 (proteins encoded by other ciliopathy genes) are primarily components of centriolar satellites, the particles surrounding centrosomes and basal bodies. RNA interference experiments reveal that satellite integrity is mutually dependent upon each of these proteins. Upon satellite dispersal, through mitosis or forced microtubule depolymerization, OFD1 and CEP290 remain centrosomal, whereas BBS4 and PCM-1 do not. OFD1 interacts via its fifth coiled-coil motif with the N-terminal coiled-coil domain of PCM-1, which itself interacts via its C-terminal non-coiled-coil region with BBS4. OFD1 localization to satellites requires its N-terminal region, encompassing the LisH motif, whereas expression of OFD1 C-terminal constructs causes PCM-1 and CEP290 mislocalization. Moreover, in embryonic zebrafish, OFD1 and BBS4 functionally synergize, determining morphogenesis. Our observation that satellites are assembly points for several mutually dependent ciliopathy proteins provides a further possible explanation as to why the clinical spectrum of OFD1, Bardet–Biedl and Joubert syndromes overlap. Furthermore, definition of how OFD1 and PCM-1 interact helps explain why different OFD1 mutations lead to clinically variable phenotypes.